Computation of zone-level ventilation requirement based on actual occupancy, plug and lighting load information. Issue 4 (April 2020) - Anand, Prashant; Cheong, David; Sekhar, Chandra
This paper presents a case study to compare the zone-level actual supplied ventilation rate with minimum required ventilation rate for a typical variable air volume (VAV) operation. The minimum required ventilation rate was computed using zone-level actual occupancy, plug and lighting load data. Two different algorithms were adopted to collect the actual zone-level occupancy information using camera-based technology which are (a) area-based occupancy counting and (b) row-based occupancy counting. Similarly, zone-level Plug, lighting and air-conditioning and mechanical ventilation (ACMV) system-related energy data were taken from the energy submeters and BTU meters. The median values of actual supplied ventilation rates are 0.16, 0.14, 0.14 and 0.12 m 3 /s for the classroom, computer room, open office and closed office, respectively. For the same zone, the computed minimum required ventilation rates are 0.10, 0.09, 0.10 and 0.08 m 3 /s, respectively. This case study shows that except during evening classes in classroom and computer room, the actual ventilation supplied is much more than the minimum required ventilation. These over and under ventilation scenarios have been identified as an indicator for energy wastage and poor indoor environmental quality, respectively.